Balance Training With Vibrotactile Neurofeedback and Ginkgo Biloba Extract in Age-Related Vertigo - Decker, Lars; Basta, Dietmar; Burkart, Martin; Ernst, Arne (Frontiers in Neurology, 2021)
Background Balance training with vibrotactile neurofeedback (VNF) can improve balance and subjective impairment in presbyvestibulopathy. Ginkgo biloba dry extract EGb 761 has been shown to improve subjective impairment in chronic vertigo and the efficacy of conventional balance training. The combination was expected to work synergistically in this difficult-to-treat population. Objectives To demonstrate the efficacy of VNF added to EGb 761 for presbyvestibulopathy. Design Multicenter, prospective, controlled, randomized, single-blind, two-arm trial (German Clinical Trials Register https://www.drks.de No.: DRKS00007633). Setting Specialist offices and tertiary care outpatient department. Participants 120 subjects aged 60+ years with chronic dizziness for over 3 months, a Dizziness Handicap Inventory (DHI) Sum Score > 25 and fall risk in balance-related situations as measured by the geriatric Standard Balance Deficit Test Composite Score (gSBDT-CS) > 40. Patients with other distinct vestibular pathology (e.g., Meniére’s disease, stroke, BPPV) were excluded. Intervention EGb 761 (80 mg twice daily for 12 weeks) plus 10 days of individually adapted balance training with VNF, randomized 1:1 to sensitive (active) or non-sensitive (sham) neurofeedback. Measurements The change in gSBDT-CS after 6 weeks (primary), other gSBDT outcomes, DHI, cognition, hearing, and safety. Results 109 of 120 enrolled subjects received both treatments at least once. Over 12 weeks, the gSBDT-CS improved by 6.7 (active) versus 4.5 (sham). There was a tendency in favor of the active treatment showing a difference of -2.4 (95% CI -5.4; 0.6) after 6 weeks. Under active treatment, more pronounced effects occurred in all secondary analyses and in nearly all secondary endpoints. The DHI sum score decreased from 44.1 to 31.1 in the total sample with a treatment group difference after 6 weeks of -3.1, 95% CI (-7.1; 0.9). No safety issues were reported. Conclusion Over 12 weeks, the combination of balance training with VNF and Ginkgo biloba dry extract EGb 761 reached a clinically relevant improvement of presbyvestibulopathy with a good pharmacological safety profile.